Beneficial effects of liraglutide on peripheral blood vessels - Zhang, Xueyang; Wang, Yongbo; Yang, Simengge; Zong, Junwei; Wang, Xuejiao; Bai, Ran (Vojnosanitetski pregled, 2022)
Background/Aim. Macroangiopathy is the major cause of death and disability in type 2 diabetic patients. Studies have shown that liraglutide, a glucagon-like peptide 1 (GLP-1) receptor agonist, can protect cardiovascular system by inhibiting chronic inflammation of diabetes. However, a study about the effects of liraglutide on peripheral blood vessels and peripheral blood leukocytes has not been reported yet. The aim of this study was to determine vasculoprotective effect, vascular protection and mechanism of action of liraglutide in addition to its hypoglycemic effect. Methods. A total of 60 hospitalized patients with type 2 diabetes were recruited from December 2013 to December 2014 at the First Affiliated Hospital of Dalian Medical University, PR China. Before the treatment with liraglutide, height and weight were measured to calculate body mass index (BMI). Blood urea nitrogen (BUN) and so on were detected. Homeostasis model assessment of insulin resistance (HOMA-IR) and islet β cell function (HOMA-β) were computed. After applying liraglutide for three months, all indexes were measured again. The effects of liraglutide on these indexes were analyzed by paired sample t-test. Results. After the treatment with liraglutide, values of glycosylated hemoglobin ‒ HbA1c (8.46 ± 1.62 vs. 7.26 ± 1.40%) and 2h postprandial blood glucose ‒ 2hPBG (11.95 vs. 9.6 mmol/L) decreased significantly (p < 0.05). Body weight (87.3 vs. 82.5 kg) and BMI (30.37 vs. 28.63 kg/m2) decreased by 5.5% and 5.7%, respectively (p < 0.05). Also, levels of triglycerides (TG) (2.57 ± 1.54 vs. 1.81 ± 0.70 mmol/L) and LDL-cholesterol (2.92 ± 0.78 vs. 1.89 ± 0.66 mmol/L) reduced significantly (p < 0.05). Ankle-brachial index (ABI) decreased from 1.24 ± 0.10 to 1.14 ± 0.06 cm/s by 8%, while brachial-ankle pulse wave velocity (ba-PWV) decreased from 1,442.15 ± 196.26 to 1,316.85 ± 146.63 cm/s by 8.7%, and both differences were statistically significant (p < 0.001). Conclusion. Liraglutide, with a good hypoglycemic effect, can significantly reduce postprandial blood glucose and HbA1c, but cannot significantly improve fasting plasma glucose, insulin resistance and islet β cell function. It also considerably decreased body weight, BMI and TG. Liraglutide can significantly lower ba-PWV and ABI to protect peripheral blood vessels.
Keywords: ankle-brachial index; arterioles; blood vessels; body mass, index; capillaries; diabetes mellitus, type 2; leukocytes; lipids; liraglutide; venules